Counseling and educational research : evaluation and application - Houser, Rick. (Unites States of America : Sage Publications, Incorporation, 2015)
The intent of this text is to prepare students in counseling and educational graduate programs to be good users and consumers of research. Our society holds science and decisions based on sound information as crucial and even uses such standards in determining culpability for malpractice.
Section1. Introduction to the research process -- Section2. Evaluating articles in the professional literature -- Section3. Application of research and evaluation .
Includes bibliographical references and index.
Keywords: EDUCATIONAL RESEARCH